2019
DOI: 10.1111/tgis.12545
|View full text |Cite
|
Sign up to set email alerts
|

Spatial optimization for land acquisition problems: A review of models, solution methods, and GIS support

Abstract: This article reviews the interdisciplinary research field of spatial optimization for land acquisition problems. We start with a theoretical framework to identify three categories of spatial optimization models: problems with aspatial constraints, location models, and problems with topological constraints. Exact, heuristic, and metaheuristic approaches to solving these problems are critically discussed. Tools that are available in commercial and open‐source GIS packages are reviewed from four aspects. We first… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 162 publications
(197 reference statements)
0
9
0
Order By: Relevance
“…Land use optimization has been broadly studied in the past decades towards various concerns or objectives [5][6][7][8][9][10][11][12][13][14]. However, there has not been many studies specifically on the livability oriented land use optimization except some general discussions and interpretation on livability from various perspectives of researchers.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Land use optimization has been broadly studied in the past decades towards various concerns or objectives [5][6][7][8][9][10][11][12][13][14]. However, there has not been many studies specifically on the livability oriented land use optimization except some general discussions and interpretation on livability from various perspectives of researchers.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In the Ministry of Land and Resources Ministry which actively promote the cities and municipalities, the integrated management of land resource center text information system is conducive to the information construction of land resources, construction of land resource information system, and information modeling of land resources which can ensure the effectiveness and efficiency of business; in recent years, land resource management did make sufficient progress and achievements, but compared to the internationalization of land resource information, there is still a certain gap in the development of land information management information technology research which is late, the basic information resources are relatively poor, and national resources and land capital are rich, but the real degree of lack of certain management, the government's limited level of management cognition, and lack of certain investment in reform courage as well as boldness, coupled with the relative lack of talent in this area, for the construction of land resource information technology has not do persistent research and accumulation, the lack of construction experience leads to the lag behind the information technology infrastructure; the overall level of information technology is low [14]. These gaps also need to be improved step by step by subsequent research scholars, and a series of problems currently encountered are mainly shown below.…”
Section: Related Workmentioning
confidence: 99%
“…a limited budget or lower bounds on environmental effectiveness) and spatial constraints (e.g. BMPs or land uses A and B must not be close to each other, Wu et al, 2018; Xiao and Murray, 2019). Spatial constraints are closely related to the type of BMP configuration unit selected and taking them into consideration is vitally important in ensuring that the optimization problem and its solutions have meaningful geographical interpretations; the solutions need to be reasonable and practical (Cova and Church, 2000; Qin et al, 2018; Yao et al, 2018; Zhu et al, 2019a).…”
Section: Introductionmentioning
confidence: 99%
“…However, taking grid cells as basic BMP configuration units generally means a large number of geographic decision variables; this will render the spatial optimization problem extremely computational-intensive or even unsolvable (Gaddis et al, 2014). Thus, grid cells are only applicable when optimizing one BMP type (Limbrunner et al, 2013; Perez-Pedini et al, 2005) in study areas with a small count of grid cells (Xiao and Murray, 2019).…”
Section: Introductionmentioning
confidence: 99%